2013
DOI: 10.1007/s11845-013-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

Initial results from the newborn hearing screening programme in Ireland

Abstract: Over 11,738 babies have been screened for permanent childhood hearing impairment (PCHI) during the first 12 months. The percentage of eligible babies offered hearing screening was 99.2 %. Only 0.2 % (n = 25) of those offered screening declined. 493 (4 %) were referred for immediate diagnostic audiological assessment. The average time between screen and diagnostic audiology appointment was 2 weeks. 15 (1.3/1,000) babies have been identified with a PCHI over the 12-month period. 946 (4 %) babies screened were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Most studies did not report follow-up after completion of UNHS and diagnostic testing ( n = 21). Of the 11 studies with any follow-up, nine attempted to follow-up the entire study population, one only reported targeted surveillance results for screen negative children with risk factors (O’Connor) [30] and one study only followed up true positive children (Antoni) [23]. Thus there were 10 studies with follow-up of screen negative children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies did not report follow-up after completion of UNHS and diagnostic testing ( n = 21). Of the 11 studies with any follow-up, nine attempted to follow-up the entire study population, one only reported targeted surveillance results for screen negative children with risk factors (O’Connor) [30] and one study only followed up true positive children (Antoni) [23]. Thus there were 10 studies with follow-up of screen negative children.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies [30, 40, 59], information was provided on UNHS-detected PCHL prevalence by NICU admission status. Pooled PCHL prevalence was 5.9 (95% CI: 3.8, 8.4) per 1000 screened children admitted to NICU, compared with 0.8 (95% CI: 0.4, 1.4) per 1000 not admitted: a PCHL prevalence rate ratio of 6.9 (95% CI: 3.8, 12.5) (Fig 5).…”
Section: Resultsmentioning
confidence: 99%
“…Historically, support for this target condition was established through evidence linking the provision of early intervention for these children with improved speech and language outcomes [1]. As this criterion is uniform across all UNHS programs, significant research has been dedicated to finding the optimal assessment pathways for these children [1][2][3][4][5][6][7][8]. However, through the same hearing screening process, many infants and children have also been identified with a hearing loss that does not fall into the target category.…”
Section: Introductionmentioning
confidence: 99%
“…2) Two sub-classifications of CHL were infrequently reported within UNHS programs (3). The audiological management of CHL within UNHS involved many and varied audiological assessments, typical in the assessment of PCHL.…”
mentioning
confidence: 99%
“…the kind of tests, number of screening steps before diagnostic referral, newborns' age when tests are performed, the professionals that administer the tests, screening location, or the targeted population). [9][10][11][12][13][14][15][16][17][18][19][20][21][22] This study provides an overview of the organisational designs of national and regional newborn hearing screening programmes in the 28 European Union (EU) countries and highlights their similarities and differences in level of policy-decision, financing, general designs, and organisational features. The ultimate goal is to initiate a network of shared practices in order to improve knowledge and practices.…”
Section: Introductionmentioning
confidence: 99%